Generation and basic characterization of bagasse from the mezcal agribusiness in Oaxaca - Flores-Ríos, Paulina Alejandra; Celerino, Robles; Castañeda-Hidalgo, Ernesto (Revista Mexicana de Ciencias Agrícolas, 2020)
In Oaxaca, in 2019, 90.1% of the certified mezcal produced domestically was produced, in addition to an unknown amount of non-certified mezcal, which in its production generates waste, bagasse the most important. Although it is currently underutilized in Oaxaca, there are various investigations into its potential, which have been aimed at obtaining various products and metabolites for industrial use. The exact data on the amount generated in the palenques and their characteristics is unknown; however, it is important information since it is the basis for establishing management strategies. In this work, carried out in the Central Valleys region of Oaxaca during 2017, the basic characterization of the solid residues of the mezcal agribusiness by species used is presented, and coefficients that can be applied for general estimation of rapid production are estimated of these residues, and serve as a basis for management strategies. It is concluded that there are differences in the characteristics of the residues and the amount of bagasse generated between the different evaluated species.
Keywords: Agave angustifolia; Agave karwinskii; Agave marmorata; Agave potatorum; agro-industrial waste; maguey mezcaleros